Thermophysical Characteristics of Tropical Fruits in Milk Powder Products - Igor A. Korotkiy; Evgeny N. Neverov; Alexander A. Vladimirov; Olga A. Neverova; Larisa A. Proskuryakova (Техника и технология пищевых производств)
Introduction. Canning requires thermophysical calculations for thermal or cold processing. These calculations are based on thermophysical characteristics of raw materials. The research objective was to analyze the thermophysical characteristics of tropical fruits. Study objects and methods. The study featured kiwi, papaya, avocado, and figs. Their thermal conductivity was analyzed with the help of stationary fiber plate method. The cryoscopic temperature was determined from the flat area of the thermogram obtained during freezing. The heat capacity and the amount of frozen moisture were determined by calculation based on the available data on the chemical composition of the fruits. The density was defined by using the hydrostatic weighing method, the sugar content – by the refractometric method, the moisture content – by drying to constant mass. Results and discussion. The research revealed the physicochemical parameters of kiwi, avocado, papaya, and figs. Papaya demonstrated the highest moisture content – 86.32 ± 0.02%, while kiwi appeared to have the highest density – 1,065 ± 1 kg/m3. Figs had the highest sugar content – 16.0 ± 0.1%. The thermal conductivity coefficient of fresh and frozen tropical fruits was determined experimentally and increased after freezing. Frozen avocado showed only a slight increase in thermal conductivity coefficient because of its low moisture content while frozen figs demonstrated a significant increase in the thermal conductivity coefficient – by 3.3 times. This product possessed the highest thermal conductivity: 0.63 ± 0.02 W/(m·K) for the fresh samples and 2.06 ± 0.02 W/(m·K) for the frozen samples. The thermal conductivity coefficient of kiwi and papaya increased by 2 and 4.2 times, respectively. The experiment also examined the effect of protective plastic wrap and ripeness on the thermal conductivity coefficient. The film proved to have a negative effect on the reliability of thermophysical analysis. The cryoscopic temperature was determined empirically. Such thermophysical properties as heat capacity, thermal diffusivity, and frozen moisture were based on the available chemical composition. Conclusion. The research revealed the physicochemical parameters of kiwi, avocado, papaya, and figs. It included a set of experiments on the thermal conductivity coefficient of fresh and frozen tropical fruits. The obtained values can be used to develop the optimal parameters of thermal processing, refrigeration, and thermal treatment of new products. They can also be useful for fortifying dairy and bakery products with exotic fruits.